A systematic view on medical informatics - Hasman, Arie; Haux, Reinhold; Albert, Adelin (Computer methods and programs in biomedicine, 1996)
Medical informatics is defined as the scientific discipline concerned with the systematic processing of data, information and knowledge in medicine and health care. The domain of medical informatics (including health informatics), its aim, methods and tools, and its relevance to other disciplines in medicine and health sciences are outlined. It is recognized that one of the major tasks of medical informatics is modelling processes. In this context, biological, communication, decision, engineering, educational, organizational and computational processes are distinguished and described.